Amnesty International dan Penghapusan Hukuman Mati di Malaysia - Sianturi, Yanti Kristina; Khurun'in, Irza (Jurnal Transformasi Global, 2020)
Malaysia is a country where the death penalty is still present and frequently practiced. It is due to different understandings of the death penalty itself. The absence of the Malaysian government in various international human rights treaties also increases unfair trials on death row inmates. The high number of death row inmates in Malaysia represents a severe human rights violation. The abolition of the death penalty is one of the current global human rights agendas. It goes against the right to live regulated by various international human rights instruments, such as the ICCPR (International Covenant on Civil and Political Rights) and the Declaration of Human Rights. One of the INGOs actively advocating the abolition of the death penalty in Malaysia is Amnesty International. This study looks at Amnesty International’s transnational advocacy tactics in encouraging the death penalty abolition in Malaysia from 2015 to 2018. The method used is descriptive research by collecting primary and secondary data and using transnational advocacy networks by Keck and Sikkink. The results of this research show that the efforts used by Amnesty International in this advocacy include information politics, symbolic politics, leverage politics, and accountability politics.